Europe in movement: Migration from/to Central and Eastern Europe - Marek Okólski (University of Warsaw, Centre of Migration Research (CMR), 2007)
Countries in Central and Eastern Europe seem to be slower than other European countries in reversing their migration character - from net emigration to net immigration. In the past, migratory movements were governed by political events and institutional constraints that impeded free access to foreign labour markets. Yet of late, and particularly since the beginning of the process of transition and the accession to the larger European economic sphere, the migration environment underwent a change. An outflow from several Central and Eastern European countries has been gaining momentum, and at present the process is characterised by several novel features that may signal a migration 'breakthrough.' It is now quite realistic to expect that emigration will relieve manpower surpluses in these countries, and that in a dozen or so years they will become - thanks to dynamic growth and economic modernization, which, in turn, could be impacted by the repercussions of present-day emigration - steady demanders of foreign labour. This paper portrays a preliminary sketch of this evolution.
Keywords: 330; Internationale Migration; Osteuropa; EU-Mitgliedschaft